Banking Reforms in Algeria: The Central Role of the Monetary and Banking Council and Banking Committee Under New Legislation - AHMED NOUI; FATMA ZOHRA GUEDOUARI (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
Economic crises ensued due to plummeting oil prices, prompting a gradual withdrawal of the state from economic activities and a shift in its role from interventionist to regulatory, manifested In the creation of entities such as autonomous regulatory agencies.